Antibody‐mediated rejection despite inhibition of terminal complement. (20th August 2014) - Bentall, Andrew; Tyan, Dolly B.; Sequeira, Flavia; Everly, Matthew J.; Gandhi, Manish J.; Cornell, Lynn D.; Li, Han; Henderson, Nicole A.; Raghavaiah, Suresh; Winters, Jeffrey L.; Dean, Patrick G.; Stegall, Mark D.
Summary Terminal complement blockade has been shown to decrease the incidence of early acute antibody‐mediated rejection (eAMR) in the first month after positive cross‐match kidney transplant recipients, yet some patients still develop eAMR. The current study investigated possible mechanisms of eAMR despite eculizumab treatment. Of the 26 patients treated with eculizumab, two developed clinical eAMR and another patient developed histologic signs of eAMR without graft dysfunction ('subclinical eAMR'). Twenty‐three did not have histologic injury on early surveillance biopsies. All 26 patients had therapeutic levels of eculizumab and showed complete blockade of complement in hemolytic assays. High levels of donor‐specific alloantibody (DSA) including total IgG, IgG3, and C1q+ DSA were present in patients with and without eAMR, and none correlated well with eAMR. In contrast, IgM DSA was present in only four patients after transplantation: the two patients with clinical eAMR, one patient with subclinical AMR, and one patient without eAMR (P = 0.006 correlation with eAMR). Both clinical eAMR episodes were easily treated with plasma exchange which removed IgM more completely and rapidly than IgG, resulting in normalization of function and histology. These data suggest a possible role of antidonor IgM DSA in the pathogenesis of eAMR in patients treated with terminal complement blockade (ClinicalTrials.gov Identifier: NCT00670774).